2018
DOI: 10.1371/journal.pone.0201871
|View full text |Cite|
|
Sign up to set email alerts
|

Possible requirement of executive functions for high performance in soccer

Abstract: In open-skill sports such as soccer, the environment surrounding players is rapidly changing. Therefore, players are required to process a large amount of external information and take appropriate actions in a very short period. Executive functions (EFs)—the cognitive control processes that regulate thoughts and action—are needed for high performance in soccer. In this study, we measured the EFs of young soccer players aged 8–11 years, who were applying for admission to an elite youth program of a Japanese Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
62
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 38 publications
13
62
3
4
Order By: Relevance
“…Despite previous research showing a positive relationship between EF and sporting expertise (i.e., the higher the EF the more expert the performer, Sakamoto et al, 2018), this study showed that in elite populations, just like in a general population, improved EF are likely a result of the maturation of the central nervous system (Zelazo et al, 2004), rather than a result of increased exposure to high level sport. Additionally, EF likely adhere to the 'threshold hypothesis', where increases in EF are only related to performance below a certain EF threshold.…”
Section: (Thres)hold My Beer While I Use Executive Functions As a Talcontrasting
confidence: 99%
“…Despite previous research showing a positive relationship between EF and sporting expertise (i.e., the higher the EF the more expert the performer, Sakamoto et al, 2018), this study showed that in elite populations, just like in a general population, improved EF are likely a result of the maturation of the central nervous system (Zelazo et al, 2004), rather than a result of increased exposure to high level sport. Additionally, EF likely adhere to the 'threshold hypothesis', where increases in EF are only related to performance below a certain EF threshold.…”
Section: (Thres)hold My Beer While I Use Executive Functions As a Talcontrasting
confidence: 99%
“…We evaluate our players' EF performance relative to their age group norms. However, there is a high variation between players on EFs across each age group, and this has similarly been reported in another study (Sakamoto et al, 2018). Our practitioners report that players who are the true elite academy players that yield the potential to make it to the adult professional level are also the players who are outperforming their age-group in the EF assessments, and the variation is caused by the many athletes that do not yet hold this "elite" status amongst coaches.…”
Section: What Inferences Can Currently Be Made From Ef Results?supporting
confidence: 83%
“…Some strategies have been recommended in the literature. For example, Sakamoto et al (2018) created a composite score by changing the results of each individual test into a z-score and then adding the z-scores together. In a practical sense, the idea of creating a single number that encompasses different scales for each variable can make the results easier to interpret and can be relatively easy to implement.…”
Section: Communicating the Resultsmentioning
confidence: 99%
See 2 more Smart Citations